2018
DOI: 10.32394/rpzh.2019.0049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugated linoleic acid and different type of dietary fat on serum lipid profile, liver enzymes activity and oxidative stress markers in wistar rats

Abstract: Background. Nutritional recommendations emphasize the need to limit consumption of saturated fatty acids and to increase the intake of polyunsaturated fatty acids in the prevention of non-communicable chronic diseases, particularly cardiovascular diseases. Among the fatty acids with health-related effects on the body, conjugated fatty acids are mentioned (i.e. CLA). Objective. The current study was designed to determine the effects of conjugated linoleic acid (CLA) on serum lipid profile, glucose, liver enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This is similar to the research by Franczyk-Żarów et al and de Angelis-Pereira et al which showed that margarine administration was able to significantly increase TG levels in experimental animals. Meanwhile, liquid butter was able to lower HDL levels better than liquid margarine [15], [16]. Atherogenic index is a potential marker for metabolic-related diseases.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the research by Franczyk-Żarów et al and de Angelis-Pereira et al which showed that margarine administration was able to significantly increase TG levels in experimental animals. Meanwhile, liquid butter was able to lower HDL levels better than liquid margarine [15], [16]. Atherogenic index is a potential marker for metabolic-related diseases.…”
Section: Resultsmentioning
confidence: 99%